Karakteristik Fisik Bahan Bakar Alternatif Campuran Minyak Jarak (CJO)-Minyak Cengkeh - gamayel, adhes (Semesta Teknika, 2016)
Crude jatropha oil (CJO) is non edible oil that made up of triglycerides. That molecules due to CJO has high viscosity and low evaporation rate. Blending with more viscous and more volatile fuel can reduce it. In this study, CJO was blended with clove oil (CO) in many precentagesi.e. 5%, 10%, 15% and 20%. The basic fuel properties such as viscosity, heating value, and flash point were measured in accordance ASTM D445, ASTM D240, ASTM D93 respectively. The results indicate that the viscosity and the Â flash point decrease while the heating value increase with an increase of concentration of clove oil. Thoseproperties have been improved because molecular interaction between eugenol and triglyceride makes molecule movement more active than before.